Therapeutic immunisation plus cytokine and hormone therapy improves CD4 T-cell counts, restores anti-HIV-1 responses and reduces immune activation in treated chronic HIV-1 infection - Herasimtschuk, Anna; Downey, Jocelyn; Nelson, Mark; Moyle, Graeme; Mandalia, Sundhiya; Sikut, Rein; Adojaan, Maarja; Stanescu, Ioana; Gotch, Frances; Imami, Nesrina (Vaccine, 2014)
This randomised, open label, phase I, immunotherapeutic study investigated the effects of interleukin (IL)-2, granulocyte-macrophage colony-stimulating factor (GM-CSF), recombinant human growth hormone (rhGH), and therapeutic immunisation (a Clade B DNA vaccine) on combination antiretroviral therapy (cART)-treated HIV-1-infected individuals, with the objective to reverse residual T-cell dysfunction. Twelve HIV-1+ patients on suppressive cART with baseline CD4 T-cell counts >400cells/mm3 blood were randomised into one of three groups: (1) vaccine, IL-2, GM-CSF and rhGH (n=3); (2) vaccine alone (n=4); or (3) IL-2, GM-CSF and rhGH (n=5). Samples were collected at weeks 0, 1, 2, 4, 6, 8, 12, 16, 24 and 48. Interferon (IFN)-γ, IL-2, IL-4 and perforin ELISpot assays performed at each time point quantified functional responses to Gag p17/p24, Nef, Rev, and Tat peptides; and detailed T-cell immunophenotyping was undertaken by flow cytometry. Proviral DNA was also measured. Median baseline CD4 T-cell count was 757cells/mm3 (interquartile range [IQR] 567–886cells/mm3), median age 48 years (IQR 42–51 years), and plasma HIV-1-RNA <50copies/ml for all subjects. Patients who received vaccine plus IL-2, GM-CSF and rhGH (group 1) showed the most marked changes. Assessing mean changes from baseline to week 48 revealed significantly elevated numbers of CD4 T cells (p=0.0083) and improved CD4/CD8 T-cell ratios (p=0.0033). This was accompanied by a significant reduction in expression of CD38 on CD4 T cells (p=0.0194), significantly increased IFN-γ and IL-2 production in response to Gag (p=0.0122) and elevated IFN-γ production in response to Tat (p=0.041) at week 48 compared to baseline. Subjects in all treatment groups showed significantly reduced PD-1 expression at week 48 compared to baseline, with some reductions in proviral DNA. Multifarious immunotherapeutic approaches in the context of fully suppressive cART further reduce immune activation, and improve both CD4 T-lymphocyte counts and HIV-1-specific T-cell responses (NCT01130376).